THE EFFECT OF MINIMUM WAGES, AND THE GENDER DEVELOPMENT INDEX ON LABOR PRODUCTIVITY IN INDONESIA - Niko Annas Hidayat; Siti Aisyah (Universitas KH. Abdul Chalim Mojokerto, 2026)
Workforce productivity serves as a fundamental gauge of macroeconomic achievement, as it captures how effectively and qualitatively human capital transforms inputs into measurable output. This research is designed to investigate the influence of statutory minimum wages, the Gender Development Index (GDI), export activity, import activity, and mean per capita expenditure on labor productivity across Indonesia throughout the 2018–2023 timeframe. The study utilizes secondary panel data, integrating cross-sectional observations from six provinces with longitudinal data spanning six consecutive years. To assess the intervariable dynamics, panel regression analysis is conducted through the Common Effect Model (CEM). The empirical findings reveal that minimum wage levels exert a positive and statistically significant impact on labor productivity, implying that wage increases are associated with improvements in worker effectiveness and overall efficiency. Average Per Capita Expenditure also shows a positive and significant effect and emerges as the most dominant variable influencing productivity. In contrast, the Gender Development Index, Exports, and Imports do not exhibit statistically significant effects during the observed period. These findings imply that improvements in wage policy and economic welfare play a more direct role in increasing labor productivity than trade activities and gender development indicators in the short term.